Status and trends of terrestrial arthropod abundance and diversity in the North Atlantic region of the Arctic - Gillespie, Mark A. K. (Ambio, 2019)
The Circumpolar Biodiversity Monitoring Programme (CBMP) provides an opportunity to improve our knowledge of Arctic arthropod diversity, but initial baseline studies are required to summarise the status and trends of planned target groups of species known as Focal Ecosystem Components (FECs). We begin this process by collating available data for a relatively well-studied region in the Arctic, the North Atlantic region, summarising the diversity of key terrestrial arthropod FECs, and compiling trends for some representative species. We found the FEC classification system to be challenging to implement, but identified some key groups to target in the initial phases of the programme. Long-term data are scarce and exhibit high levels of spatial and temporal variability. Nevertheless, we found that a number of species and groups are in decline, mirroring patterns in other regions of the world. We emphasise that terrestrial arthropods require higher priority within future Arctic monitoring programmes. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s13280-019-01162-5) contains supplementary material, which is available to authorized users.